2004
DOI: 10.1175/1520-0442(2004)017<0727:ccbtna>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Characteristics between the Northward and Eastward Propagation of the Intraseasonal Oscillation during the Boreal Summer

Abstract: This study investigates the structural and evolutionary characteristics of the eastward-and northward-propagating intraseasonal oscillation (ISO) in the Indian Ocean and western Pacific during the boreal summer. Along the equator, the near-surface moisture convergence located to the east of the deep convection region appears to result in the eastward propagation of the ISO, consistent with the frictional wave-CISK (conditional instability of the second kind) mechanism proposed in previous studies. The eastward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…A positive equivalent barotropic vorticity perturbation and enhanced specific humidity in the lower troposphere are found to lead the convection center by a few degrees. The northward shift of low-level moisture perturbation relative to the BSISV convection, which may suggest a pre-conditioning process for its northward propagation, has also been illustrated by other observational studies (e.g., Hsu et al 2004;Fu et al 2006). Jiang et al (2004) further proposed an ''easterly vertical wind shear'' mechanism to explain the northward propagation of the BSISV, in which the easterly vertical shear of the zonal mean flow over the Asian monsoon region could play a fundamental role.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…A positive equivalent barotropic vorticity perturbation and enhanced specific humidity in the lower troposphere are found to lead the convection center by a few degrees. The northward shift of low-level moisture perturbation relative to the BSISV convection, which may suggest a pre-conditioning process for its northward propagation, has also been illustrated by other observational studies (e.g., Hsu et al 2004;Fu et al 2006). Jiang et al (2004) further proposed an ''easterly vertical wind shear'' mechanism to explain the northward propagation of the BSISV, in which the easterly vertical shear of the zonal mean flow over the Asian monsoon region could play a fundamental role.…”
Section: Introductionsupporting
confidence: 56%
“…While the eastward propagating MaddenJulian Oscillation (MJO;Julian 1971, 1994) is found to be a dominant ISV form in boreal winter, the boreal summer ISV (BSISV), with a period of 30-50 days, is characterized by a pronounced northward propagation over the Asian monsoon region (e.g., Yasunari 1979;Hsu and Weng 2001;Lawrence and Webster 2002;Hsu et al 2004;Jiang et al 2004;Jiang and Li 2005;Goswami 2005;Wang et al 2005;Waliser 2006; and many others). The meridional propagation of the BSISV is found to be intimately associated with active and break phases of the Asian summer monsoon (e.g., Sikka and Gadgil 1980;Cadet 1986;Lawrence and Webster 2002).…”
Section: Introductionmentioning
confidence: 99%
“…proposed mechanisms including vertical wind shear over monsoon region, vorticity advection, moisture advection and air-sea interaction via surface fluxes for northward propagation of BSISO. Study by Hsu et al (2004) showed that moisture convergence and surface sensible heating may contribute to northward propagation of convection in the Indian Ocean, while frictional convergence is the dominant factor for eastward propagation. Another study by Chou and Hsueh (2010) proposed that mechanisms contributing to northward propagation are different both in Indian Ocean and west Pacific sectors mainly due to the different land-sea distribution and underlying surface processes.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (2004) proposed a mechanism by which the vertical shear and moisture-convection feedback aids the northward propagation of BSISO. Meanwhile studies like Hsu et al (2004) put forward different mechanism for northward and eastward propagation in boreal summer. Most of the proposed mechanisms for eastward propagation are based on the equatorial wave dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their study shows that the northward migration of precipitation anomalies is caused by this vertical shear mechanism. Hsu et al (2004Hsu et al ( , 2005 suggest that the eastward extension of the northward propagating precipitation anomalies from the Arabian Sea could be driven by the anomalous surface convergence located to the east of the deep convection region, which is in turn induced by the lifting and frictional effects of the geography over the west coast of the Indian subcontinent. Rossby wave response to heating sources over the equatorial Indian Ocean have been linked in remotely enhancing the northward propagating precipitation anomalies (Lawrence and Webster 2002;Annamalai and Sperber 2005).…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%